Design of Hybrid-driving Transmission System of Hobbing Machine - Tan Weiming (Jixie chuandong)
An inner-linked transmission train based on hybrid- driving is proposed for the gear generating transmission train of the hobbing machine to solve the two main problems of gear generation and helix differential in designing transmission system of the hobbing machine.By using a 2 DOF differential gear mechanism as the motion composition mechanism,a mechanical transmission movement and an electronic- driven movement are combined to achieve combination of rough adjustment and fine adjustment.Based on the method of hybrid- driving,the transmission system of the hobbing machine is designed in details,with its hobbed gear tooth numbers being 11110.According to the design result,the requests for generating motion in gear hobbing machine could be satisfied.